Resolusi Konflik Terhadap Pesta Demokrasi (Analisis Sosio-Politik Pemilihan Kepala Daerah di Bulukumba) - Haniah, St.; Mukramin, Sam’un (Phinisi Integration Review, 2021)
Elections for Regional Heads always experience the complexity of problems that lead to prolonged social conflicts without massive evaluation to minimize them. Not a few also happened, which involved various society and government institutions that participated in the contest. The research objective was to analyze and find the resolution of conflicts in Bulukumba Regency due to the democratic party of the Regional Head General Election. The research method is presented in a descriptive qualitative form with a case study approach. Primary and secondary data sources with data collection techniques, observation, interviews, and documentation. The analysis was data carried out through reduction, presentation, verification, and conclusions based on the data's validity. Among the conflict resolutions formulated, namely: a) local wisdom is the locomotive of peace to minimize social conflicts that lead to social disintegration. The implementation stage is a collective awareness built by the local community itself as an essential building for existing values and norms, b) The adaptation roles and of institutional functions in breaking down and applying rules is a potential superior as a latent function and a real function in preventing social conflicts that will occur, both micro and macro aspects that lead to movements preventive, persuasive and repressive role, and c) To suppress behavior deviant during the democratic party process, money politics must be stopped and avoided by the existence of associative relationships between the community and local wisdom values and the government through adaptive roles and functions. Institution authorized social.